PERANCANGAN APLIKASI PERPUSTAKAAN E-BOOK BERBAYAR BERBASIS ANDROID - dominikus bugar perkasa ajie (Jurnal Informatika, 2021)
Abstract— The development of the internet and information technology is so fast that it requires conventional libraries to innovate to be closer to their users. This is also necessary to increase reading interest in people of this era who are very close to smartphones in carrying out daily activities. The Android-based digital library application offers convenience for its users in accessing information sources with an attractive and fun appearance. Users no longer need to be physically tied to service hours or have to visit conventional libraries because digital libraries can be accessed anytime and anywhere. This digital library application uses the Lavensthein algorithm method to make it easier for admins to manage library member data. Laventhein's algorithm method can manage strings with the concept of adding, deleting, and measuring, and can measure the difference between strings. This application also uses Google Drive as a storage medium for collections from digital libraries. With this digital library, it is hoped that it can become a medium that educates the public and becomes a place for writers to work. Keywords : Digital Library, Google Drive, Levensthein